2009
DOI: 10.1016/s0924-9338(09)71182-4
|View full text |Cite
|
Sign up to set email alerts
|

The Picture of Mental Disorders in Czech Printed Media

Abstract: Background and aims:It's known that media significantly contribute to the stigmatisation of mental disorders themselves, as well as the people suffering from such ailments. The aim of our study is to provide content analysis of media messages covering the topics of mental health and psychiatry.Methods:The study sample comprises the media messages pertaining to the topic of mental illness collected by using the database of the Newton IT monitoring system. The articles were chosen from 6 printed most widely read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this study, almost all news was negative toward individuals with mental disorders in the results relating to the quality of the investigated news (Figure 1). Parallel to the results of this study, it has been observed in many national and international studies that the subject of a great majority of the news found in printed and visual media is related to individuals diagnosed with schizophrenia and is negative in terms of individuals with mental disorders (Aragonès et al, 2014; Böke et al, 2007; Goulden et al, 2011; Kalucy et al, 2011; Nawková et al, 2009, 2012). News covering recovery, rehabilitation, and the positive expression and experiences of mental health professionals appears less often in the newspapers (Whitley & Berry, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, almost all news was negative toward individuals with mental disorders in the results relating to the quality of the investigated news (Figure 1). Parallel to the results of this study, it has been observed in many national and international studies that the subject of a great majority of the news found in printed and visual media is related to individuals diagnosed with schizophrenia and is negative in terms of individuals with mental disorders (Aragonès et al, 2014; Böke et al, 2007; Goulden et al, 2011; Kalucy et al, 2011; Nawková et al, 2009, 2012). News covering recovery, rehabilitation, and the positive expression and experiences of mental health professionals appears less often in the newspapers (Whitley & Berry, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…It was observed that two thirds of all news on forensic actions contained negative stigmatizing elements (Figure 3) and two thirds of the subjects’ images in the news contained stigmatizing elements (Table 6). Many studies have reported that mental disorder is portrayed as violence, crime, unpredictability, dangerousness (harming himself/herself or others), or that individuals with mental disabilities are represented as passive victims in a ‘miserable and helpless’ condition (Bilić & Georgaca 2007; Goulden et al, 2011; Kalucy et al, 2011; Nawková et al, 2009, 2012). In a study conducted by Olstead (2002) to analyze how mental disorders are represented in 195 news articles in two major Canadian newspapers, it was discovered that the most common theme was ‘psychiatric patient criminal’ and these texts included discourses separating ‘us’ (reader) from ‘them’ (individuals with mental disorders).…”
Section: Discussionmentioning
confidence: 99%
“…Stereotypes of mental illness are transmitted to the young generation and stigma is reinforced by the media. A group of Czech psychiatrists and psychologists examined articles mentioning mental illness in newspapers and journals in the Czech Republic and found that they had very negative overall tones and were likely to reflect a very high level of stigmatization of patients with mental disorder [17,18].…”
Section: Czech Republicmentioning
confidence: 99%
“…Having a mental disorder and being treated in a psychiatric institution still cause social stigmatization and the same holds true for EDs. A recent study analysed the association of social stigma and mental health in the Czech printed media, finding negative depictions of mental disorders (for example, EDs) in 37 articles, constituting 4 per cent of the 203 news articles reviewed (Nawková et al ., ). The fear of such stigmatization is strongly internalized, fuelling the reluctance many Czech families feel about psychiatric hospitals and mental healthcare in general, and family‐based interventions in particular (Izaková et al ., ; Tomanová and Papežová, ).…”
Section: Challenges and Limitations Of Multi‐family Therapy In Praguementioning
confidence: 97%